Restoring coronal pre-arthritic alignment in mobile-bearing unicompartmental knee arthroplasty: mid- to long-term outcomes - Yankun Jiang; Changquan Liu; Qidong Zhang; Guoyuan Sun; Ran Ding; Nianfei Zhang; Cheng Huang; Weiguo Wang; Wanshou Guo (BMC Musculoskeletal Disorders)
Abstract Background Previous research suggests that restoring pre-arthritic alignment in fixed-bearing unicompartmental knee arthroplasty (UKA) can improve postoperative knee function. However, its applicability to mobile-bearing UKA remains unclear. This study evaluated whether patients who achieve pre-arthritic alignment following mobile-bearing UKA with the kinematic alignment technique experience superior postoperative knee function compared with those who do not. Methods A retrospective analysis was conducted on 236 knee joints that underwent UKA using kinematic alignment techniques between May 2015 and November 2017. Of these, 222 knee joints met the inclusion criteria for the study. Postoperative outcomes were assessed, with pre-arthritic alignment determined using the arithmetic hip-knee-ankle angle (aHKAA). Postoperative alignment within ± 3° of the aHKAA was classified as pre-arthritic alignment. Patients were categorized into two groups: pre-aligned and non-pre-aligned. Final follow-up occurred in September 2024, and outcome measures included the visual analogue scale (VAS) score, Hospital for Special Surgery (HSS) score, and Knee Injury and Osteoarthritis Outcome Score (KOOS) subscales for daily living, sports, and survivorship. Additionally, the percentage of patients meeting the patient-acceptable symptom state (PASS) criteria for KOOS-related subscales was recorded. Failure was defined as conversion to total knee arthroplasty. Results Among the 222 knee joints analyzed, the average follow-up time was 8.65 years (range: 7–9 years), with an average implant survival time of 8.48 years and a total knee arthroplasty conversion rate of 2.7%. The 5-year survival rate was significantly higher in the pre-arthritically aligned group (99.4%) than in the non-pre-arthritically aligned group (92.5%) (p = 0.012). In total, 169 knees (76.13%) were classified as pre-arthritically aligned, while 53 knees (23.87%) were non-pre-arthritically aligned. postoperative VAS scores significantly improved from 6.90 ± 0.82 to 0.58 ± 0.56 (p < 0.001), and HSS scores increased from 56.3 ± 8.36 to 92.39 ± 4.54 (p < 0.001). Although no significant differences in postoperative VAS scores were observed between groups (p = 0.147), the pre-arthritically aligned group demonstrated significantly higher HSS scores and better KOOS subscale scores for daily living activities, sports, and quality of life than the non-pre-arthritically aligned group (all p < 0.01). The PASS ratio for KOOS subscales also indicated superior outcomes in the pre-arthritically aligned group. Conclusion Using the kinematic alignment technique for mobile-bearing UKA, knees that achieved pre-arthritic alignment demonstrated superior survivorship and subjective postoperative knee function compared with those that did not.